1984
DOI: 10.1051/rphysap:01984001906044500
|View full text |Cite
|
Sign up to set email alerts
|

Thermal anomaly in sodium potassium sulphate crystals

Abstract: Résumé. 2014 Les propriétés thermales du NaKSO4 cristal, que l'on a fait croître à 315 K par la méthode d'évapora-tion lente, ont

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Single crystals of (NaxK1-x)2SO4 were grown by the dynamical and slow evaporation method [4] at constant temperature of 315 K from aqueous solutions of different stoichiometric ratios of pure Na2SO4 and KzSO4. The stoichiometric ratio x was chosen to be x = 0.2, 0.3, 0.4, 0.8 and 0.9.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single crystals of (NaxK1-x)2SO4 were grown by the dynamical and slow evaporation method [4] at constant temperature of 315 K from aqueous solutions of different stoichiometric ratios of pure Na2SO4 and KzSO4. The stoichiometric ratio x was chosen to be x = 0.2, 0.3, 0.4, 0.8 and 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…In an early work, Kassem et al [4] have studied the thermal properties of NaKSO4 single crystal (x = 0.5). It has been suggested that under normal conditions, the pure NaKSO4 crystal may exhibit a structural phase transition at about 453 K. Those authors argue that the transition is probably from orthorhombic symmetry with point group mmm to monoclinic symmetry with point group 2/m.…”
Section: John Wiley and Sons Limited Chichester Akad~miai Kiad6 Budamentioning
confidence: 99%
“…Thermomechanical analysis (TMA) was carried out using a Heraeus TMA 500 dilatometer, as described previously (Kassem, Kandil, El-Wahidy and El-Gamal, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…During our previous studies of the thermal properties of NaKSO4 crystals, anomalous behaviour of the specific heat (Cp) was observed at 453 K [2]. Upon irradiation of the crystal the position of the peak representing the change in Cp with temperature, was found to vary with irradiation dose.…”
mentioning
confidence: 96%
“…Non-irradiated NaKSO4 crystals, when heated, showed an anomaly at 453K [2], as the thermal expansion coefficient measured along the Z-axis had a negative value.…”
mentioning
confidence: 99%